2020
DOI: 10.1109/tpel.2019.2961604
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Measurement of Dynamic on-State Resistances of GaN Devices Under Reverse and Forward Conduction in High Frequency Power Converter

Abstract: Because of trapped charges in GaN transistor structure, device dynamic ON-state resistance R DSon is increased when it is operated in high frequency switched power converters, in which device is possibly operated by zero voltage switching (ZVS) to reduce its turn-ON switching losses. When GaN transistor finishes ZVS during one switching period, device has been operated under both reverse and forward conduction. Therefore its dynamic R DSon under both conduction modes needs to be carefully measured to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…. More details on the measurement accuracy of the proposed measurement circuit can be found in our previous publication [28].…”
Section: Model Principle and Parameters Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…. More details on the measurement accuracy of the proposed measurement circuit can be found in our previous publication [28].…”
Section: Model Principle and Parameters Extractionmentioning
confidence: 99%
“…The advantages of TZCM are that (1) all four GaN-HEMTs can be operated under ZVS soft switching to reduce switching losses and (2) the dynamic R DSon value can be measured under constant current amplitude. Measurement error due to parasitic inductance and probe deskew on measurement results can be eliminated [28].…”
Section: Different Operation Conditionsmentioning
confidence: 99%
“…However, even though the presence of noise and offsets are reported, no suitable methods for mitigating their effect in an online setup are suggested. In [16], an estimation error of 2.9% is reported, however, the estimations are conducted under constant load, and under low-noise conditions. Similarly, in [24], online measurement of V-I curves have been compared to curve-traced measurements, however, they have shown that at nominal voltages and currents, the switching noise significantly distorts the ON-state voltage measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in order to confidently detect aging, or to precisely estimate the junction temperature, accurate estimation of the ON-state resistance is required. The ON-state resistance is typically extracted from the ON-state voltage measurements, and load current [8], [15], [16]. A multitude of considerations are needed for accurate measurement of the ON-state voltage.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], [21]- [23], depletion mode MOSFETs (DM-MOSFETs) are used for protecting the measurement circuit from the OFF-state voltage. This design is shown to also have a high bandwidth when a small resistance is placed between the gate-source terminals of the DM-MOSFETs [16]. A significant advantage with these designs is that the DM-MOSFET of the measurement circuit is a resistive channel.…”
Section: Introductionmentioning
confidence: 99%